Finite Automata - Zanella, Marina; Zhao, Xiangfu; Lamperti, Gianfranco (Introduction to Diagnosis of Active Systems, 2018)
Automata are a special class of abstract devices for computation, also called machines, which have been the subject of a vast amount of research for several decades [64].